A Meta-Analysis of Risk Factors of Length of Exposure, Smoking Habits, Use of Personal Protection Equipment (PPE), and Exposure to Welding Fumes in Welding Workers with Abnormal Pulmonary Function (A Perspective of Sustainable Public Health) - Nanda Inas Fauziyah; R Azizah; Lailia Ayu Rachmawati; Ahmad Zaharin Aris; Arif Sumantri; Siti N. A. Jauharoh; Datu Buyung Agusdinata (JURNAL KESEHATAN LINGKUNGAN, 2022)
Introduction: About 11 million workers are welders worldwide, and more than 110 million workers are exposed to welding-related jobs. As many as 75.6% of welding workers in Pontianak, West Kalimantan, Indonesia, suffer from abnormal pulmonary function due to exposure to welding fumes. This study analyzed some risk factors and their sensitivity of abnormal pulmonary function in welding workers. Methods: This study is a meta-analysis article. Data sources were obtained from articles published online on Google Scholar, Science Direct, Pubmed, and Springerfrom 2010 to 2020. A total of 15 articles were selected for meta-analysis using JASP version 0.9.2 software. Results and Discussion: Results showed pooled prevalence ratio (PR) values of long-exposure variables of 1.954 (95% CI = 0.31– 1.03), smoking habits of 2.159 (95% CI = 0.33–1.22), USE of PPE 1.491 (95% CI = -0.50–1.30) and exposure to welding fumes 2.271 (95% CI = 0.52–1.12) in welding workers with abnormal pulmonary function. Conclusion: Exposure to welding fumes and smoking habits are the highest risk factors causing abnormal pulmonary function in welding workers. For workers, it is expected to reduce or stop smoking and always use PPE at work. For industry, control efforts are required by rotating work, conducting periodic worker medical examinations, providing exhaust with blowers in the workspace, and reinforcing the use of PPE at work.